Utilization of Augmented Reality as an Interactive Media in The Learning of Fine Arts in Elementary School Education Students - Poerwanti, Jenny Indrastoeti Siti; Budiharto, Tri (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Utilization of Augmented Reality (AR) as interactive learning media can stimulate students' mindset in thinking critical because AR can visualize abstract concepts for understanding and the structure of an object model. This allows AR as a more effective medium. Augmented reality applications show good potential in giving students more active, effective and meaningful learning. Augmented Reality (AR) can be defined as a technology that can combine virtual objects two-dimensional or three-dimensional into a real environment and then bring it or project it in real time. The purpose of this study was to describe the ability of students to appreciate the results of fine art. It also aims to examine user acceptance of augmented reality applications within an art learning at primary teacher education program, from students’ opinion when AR is used in class. The research design was descriptive. The study was conducted with 30 primary school teacher education students in Universitas Sebelas Maret. Data collection techniques used in this study are portfolio and questionnaire. The results show that (1) 75% ability of students’ appreciation in appreciating art works is very good, especially in the stages of analysis and assessment, (2) Students’ opinion about AR media 87.66% said it was beneficial for art learning, because AR can motivate to produce creative works of art. These results indicate that the application of AR as an interactive learning media can improve the ability to appreciate fine art